Factors associated with the usage, disposal and elimination of personal protective equipment and other veterinary inputs in large animal practice (FAVE Sección Ciencias Veterinarias, 2019)
A cross-sectional study was carried out in 330 veterinarians working on large animal practice in the Province of Santa Fe, Argentina to estimate: a) frequency of usage and final disposal of personal protective equipment and supplies for clinical practice, b) associations with socio-demographic characteristics of the interviewees. Data analysis included: χ2, Student's t test, Fisher's exact test and Pearson's correlation coefficient. Thirty percent had been diagnosed with zoonosis (brucellosis: 27.2%). Discarding gloves on the farm was the most frequent means for disposal. One out of five practitioners eliminated the gloves along with household wastes, while four out of 10 had a similar behavior on regards of disposable needles. Practitioners´ gender and time after graduation were significantly associated with usage, disposal and elimination of veterinary inputs following various professional practices.
Keywords: lage animal practice; veterinary wastes; disposal and elimination